On importance of imperfections in plastic strain localization problems in materials under impact loading (Archives of Mechanics - Test, 2002)
The work is the continuation of Professor Piotr Perzyna achievements in the description and analysis of the phenomenon of plastic strain localization. The ductile materials under impact loading are in focus of interest. In particular, the influence of initial imperfections on the final pattern of localization is elaborated. The computer simulations were performed in the environment of ABAQUS program.